A genetic algorithm for flow shop scheduling problem (2010)
This paper considers the problem of scheduling in flow-shop by Johnson's Algorithm method and Genetic Algorithm method to find an optimal sequence for n jobs m-machine based on minimum elapsed time. It has been shown that the method for finding an optimal sequence for n jobs, m-machine based on minimum make span using genetic algorithm provides a better result.